Spelling Worktext and Performance of Grade 11 Students of Esperanza National High School - Imie M. Soquita, MAT (RIRAI Publisher, 2021)
This study examined the level of achievement in Spelling of the Grade 11 students of Esperanza National High School and acceptability of the Rule-based Spelling Worktext Module in helping the students improve their spelling competencies. It employed experimental design and utilized 50 students to the control group and 50 students to compose the experimental group. For the experimental group, the researcher used the Rule-based Spelling Worktext while Copy-Only Method was applied to the control group. After allotted weeks for spelling instruction, a post- test was conducted to see if there are significant differences on the performance of students in spelling in control and experimental groups. To solve, analyze and interpret the result of the study, percentages, mean, and z-test were used. Study showed that the acceptability level of the Rule-based Spelling Worktext based on its content, relevance and instructional aspect were all described as “Excellent.” The z-test results showed that the spelling performance of the students from the control and experimental groups was the same in pre-test but not significantly the same in post-test. This implied that the experimental group of students showed significant improvement in the post-test than in control group. This improvement in their performance in spelling could be credited to the Rule-based Spelling Worktext which was used with the experimental group in teaching spelling.